Depolymerization of Rice Straw Lignin into Value-Added Chemicals in Sub-Supercritical Ethanol - Viet T Tran; Tan M. Le; Phu V. Vu; Hien M. Nguyen; Yen H.P Duong; Phung K. Le (The Scientific World Journal)
Depolymerization of lignin is an important step to obtain a lignin monomer for the synthesis of functional chemicals. In the context of more lignin produced from biomass and pulp industry, converting real lignin with low purity is still required more studies. In this study, the influence of solvent composition and reaction parameters such as binary solvents ratio, time, and temperature, the solvent-to-lignin ratio on the depolymerization of rice straw lignin was investigated carefully. Essential lignin-degraded products including liquid product (LP), char (solid), and gas were obtained, and their yields were directly influenced by reaction conditions. Results show that the maximum lignin conversion rate of 92% and LP yield of 66% was under the condition of 275°C, 30 min, 75 : 1 (mL solvent/1 g lignin), and ethanol 50%. Gas chromatography-mass spectroscopy (GC-MS) analysis was used for the analysis of the depolymerization products and identified 11 compounds which are mainly phenolic compounds such as 2-ethylphenol, 3-ethylphenol, phenol, methyl 2,4,6-trimethylbenzoate. The structure changes of LP and char in various conditions were analyzed using Fourier-transform infrared (FTIR).